2018
DOI: 10.1098/rsfs.2017.0037
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid graphene–ceramic nanofibre network for spontaneous neural differentiation of stem cells

Abstract: A challenge in regenerative medicine is governed by the need to have control over the fate of stem cells that is regulated by the physical and chemical microenvironment and. The differentiation of the stem cells into specific lineages is commonly guided by use of specific culture media. For the first time, we demonstrate that human mesenchymal stem cells are capable of turning spontaneously towards neurogenic lineage when seeded on graphene-augmented, highly anisotropic ceramic nanofibres without special diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…We recently demonstrated that application of cells on graphene-augmented inorganic nanofiber (GAIN) scaffolds can trigger different cell reactions and mechanisms, leading to changes in their morphology, orientation, and gene expression. 30 , 46 It has been shown that some cancer cells can change their behavior depending on the substrate usage. The current work studies this effect in more precise detail.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently demonstrated that application of cells on graphene-augmented inorganic nanofiber (GAIN) scaffolds can trigger different cell reactions and mechanisms, leading to changes in their morphology, orientation, and gene expression. 30 , 46 It has been shown that some cancer cells can change their behavior depending on the substrate usage. The current work studies this effect in more precise detail.…”
Section: Resultsmentioning
confidence: 99%
“…We earlier showed that GAIN-type scaffolds have a substantial mechanical anisotropy, as measured by the tangential elastic modulus, reaching 400 GPa/5 kPa = 80 × 10 6 . 30 , 46 This range spans for example over the elasticity of F-actin filaments (∼1–5 GPa 16 ), involved in cells adhesion and taxis. This is combined with matched diameter of the nanofibers in GAIN ( Figure 1 ) to actin filaments spacing (20–30 nm) and microtubules (∼25 nm), 16 , 24 , 28 being significantly (500–1000 times) smaller than average cell sizes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors have recently demonstrated applications of unique scaffolds, composed of self-aligned graphene-augmented inorganic (alumina) nano-fibers (GAIN). Ultra-high anisotropy (over 10 6 :1) and porosity (over 90%) of fibers were shown to result in thrilling effects over the cell cultures seeded; including but not limited by the suppression of inflammatory markers in human mesenchymal stem cells (hMSC) and peripheral mononuclear blood cells [ 4 ], the neurogenic-type differentiation of hMSC without any specific differentiation media [ 5 ], and the different gene expression and the reactivity of various types of cancer cells [ 6 ]. These findings allowed to formulate a phenomenon of auto-mechanoinduction in the cells, where ultra-high mechanical anisotropy of the substrate acting on two different levels (from 10–20 nm to cm scale) has triggered unusual (mutually confusing) reactions of the cells and, as a result, unexpected gene expression and cells differentiation [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Kazantseva et al [12] take the topic of graphene-based fibres even further by showing how networks of composite graphene-ceramic fibres can be used in the control of stem cells.…”
Section: Introductionmentioning
confidence: 99%